2017
DOI: 10.1002/adhm.201700245
|View full text |Cite
|
Sign up to set email alerts
|

Taxane‐Grafted Metal‐Oxide Nanoparticles as a New Theranostic Tool against Cancer: The Promising Example of Docetaxel‐Functionalized Titanate Nanotubes on Prostate Tumors

Abstract: The combination of anticancer drugs and metal oxide nanoparticles is of great interest in cancer nanomedicine. Here, the development of a new nanohybrid, titanate nanotube-docetaxel (TiONts-DTX) is reported, the two parts of which are conjugated by covalent linkages. Unlike most nanoparticles currently being developed for biomedical purposes, TiONts present a needle-shaped morphology. The surface of TiONts is linked with 3-aminopropyl triethoxysilane and with a hetero-bifunctional polymer (polyethylene glycol)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(63 citation statements)
references
References 69 publications
5
57
1
Order By: Relevance
“…Bare TiONts were coated by APTES and PEG with protocols very similar to that used for SPIONs [8]. The method of chitosan (CT) grafting is based on electrostatic interactions between chitosan's amines and nanotubes' hydroxyl groups.…”
Section: Synthesis Of Tionts and Functionalization Of Their Surfacementioning
confidence: 99%
See 4 more Smart Citations
“…Bare TiONts were coated by APTES and PEG with protocols very similar to that used for SPIONs [8]. The method of chitosan (CT) grafting is based on electrostatic interactions between chitosan's amines and nanotubes' hydroxyl groups.…”
Section: Synthesis Of Tionts and Functionalization Of Their Surfacementioning
confidence: 99%
“…However, the subsequent surface functionalization of these nanotubes with Docetaxel reduces the drug availability and significantly increases Docetaxel IC50 in 22Rv1 cells, compared to free drug control [8]. As described in the next section, in vivo studies have shown that TiONts acts like an anchor in the tumor, which prevents drug from leaching out of the cancerous cells, and as a result, the loss in drug potency was not detrimental in this specific case [8].…”
Section: Cytotoxicity Of Tionts: the Surface Chemistry Mattersmentioning
confidence: 99%
See 3 more Smart Citations